2023
DOI: 10.3389/fmed.2023.1140339
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Sulfasalazine-induced hypersensitivity

Abstract: Drug-induced hypersensitivity syndrome (DiHS)/drug reaction with eosinophilia and systemic symptoms (DRESS) is a systemic inflammatory condition that is characterized by multisystemic involvement (liver, blood, and skin), heterogeneous manifestations (fever, rash, lymphadenopathy, and eosinophilia), and an unpredictable course; cases of DiHS/DRESS caused by sulfasalazine are rare in children compared to adults. We report a case of a 12-year-old girl with juvenile idiopathic arthritis (JIA) and sulfasalazine-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Only five out of 18 patients had normal liver function and the rest had elevated liver enzymes (ALT/AST), with more than half of the patients having liver enzymes more than twice the upper limit of normal values. Kuchinskaya et al ( 20 ) retrospectively analyzed the clinical characteristics of 16 patients with DiHS, and the results showed that all the patients had liver impairment, and no other organ impairment was seen in any patient, which is generally consistent with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Only five out of 18 patients had normal liver function and the rest had elevated liver enzymes (ALT/AST), with more than half of the patients having liver enzymes more than twice the upper limit of normal values. Kuchinskaya et al ( 20 ) retrospectively analyzed the clinical characteristics of 16 patients with DiHS, and the results showed that all the patients had liver impairment, and no other organ impairment was seen in any patient, which is generally consistent with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Although 5-ASA medications have proven clinical efficacy, some of them can cause serious side effects. For instance, sulfasalazine has been associated with drug eruptions, drug-induced hypersensitivity syndrome, and acute pancreatitis [ [4] , [5] , [6] ]. Salicylic acid preparation and immunosuppressive therapy won't cause any effective effects on some patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%